Experimental study of the strengthening efficiency of engineering waste sludge using electro-osmosis - Yanli TAO; Zeyi YU; Jianfeng ZHU; Xiaonan GONG; Jian ZHOU; Kaiqiang LI (Shuiwen dizhi gongcheng dizhi)
The intensification of urbanization has resulted in a significant increase in the generation of engineering waste sludge. Traditional treatment methods on engineering waste sludge often fail to achieve desired dewatering targets. Electroosmosis has garnered considerable attention for its substantial potential in soft ground treatment and sludge consolidation. Consequently, both domestic and international experts have studied rapid dewatering and reducing initial moisture content. However, there is still an incomplete understanding regarding the efficiency of electroosmosis. A series of experiments were performed under different potentials with Hangzhou engineering waste sludge, using ferrum and graphite electrodes. Electro-osmotic efficiency was analyzed in terms of total energy consumption, effective energy consumption, and electrode loss. The relationship between the effective energy coefficient and effective potential was explored based on the experimental results and theoretical models. It was found that total and effective energy consumptions increase with the potential. The rates of increase are larger with higher potentials. Total and effective electro-osmotic efficiency decreases with the increasing potentials. Electrode materials possess little influence on the electro-osmotic efficiency, but have indirect impact through effective potential due to the anode material loss. A linear relationship was obtained between the effective energy coefficient and effective potential. Low voltage is a disadvantage to the electro-osmotic effect, while high voltage is a disadvantage to electro-osmotic efficiency. Therefore, both the electro-osmotic effect and efficiency should be considered when determining the optimal voltage value in practice. The experimental results on the significant reduction of the energy consumption of electroosmosis can provide a scientific basis for the further promotion and application of electroosmotic technology in practical engineering projects.